Traditional Japan - Nardo, Don (San Diego, California Lucent Books, 1995)
World history series on Traditional Japan. Traces the history of Japanese civilization from legendary times through the end of the Shogunate in the nineteenth century
Island at the edge of the world -- The Nara Period -- Land and prestige -- Honor in death: the samurai and the rise of militarism -- Invasion and civil war -- Muromachi Japan -- Moats, muskets, and missionaries -- Rule of the Tokugawa.
Includes bibliography references and Index
11 - 18 years
Keywords: Japan -- History -- To 1868